Pembuatan Bibliografi Beranotasi Buku Kesenian Nusantara di Perpustakaan Jurusan Sendratasik Fakultas Bahasa dan Seni Universitas Negeri Padang - Sufi, Meilani; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed the compilation process of annotated bibliography for the books of regional custom arts in Indonesian archipelago available in the library of Art Drama Dance and Music (Sendratasik) Department, Faculty of Languages and Arts, State University of Padang. The compilation of this bibliography aimed to facilitate the library users in searching the information about the books of local arts owned by the library of Art Drama Dance and Music Department. This paper used descriptive method with the technique of data collection through direct observation―observing the physical state of the books and the collection of references available in the library of Sendratasik Department. A number of 39 books titles were used as the object of the research in accordance with the title taken by the author about the collection of archipelago art books. The samples of archipelago art books selected were compiled based on the good bibliography compilation process using American Psychological Association (APA) format comprising several stages. From the results of the discussion, it could be concluded that the compilation stages of annotated bibliography for the collection of books of regional custom arts in Indonesian archipelago were: first, the determination of the title by noticing (a) the availability of the collection, (b) the use of the collection, (c) the well-preserved information. Second, the accumulation of the library materials by noting the author's name, year of publication, title, place of publication and the publisher. Third, the selection of the library materials for matching the title of bibliography and the library materials collected. Fourth, the grouping or classification of the library materials. Fifth, the generating of keyword. Sixth, the arrangement of index. Seventh, the typing of manuscript. Eighth, the checking of the final manuscript.           Keywords: bibliography, archipelago arts, annotation